Psikhologicheskie mekhanizmy emotsional'no-volevoi samoregulyatsii v sporte - Smirnov, B. N. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
It is shown which difficulties are to be overcome in sport and how functiones the scheme of self-regulation of the individual. Conclusions for self- regulation in sport practice are drawn.